Is Bladder Cancer More Common among Opium Addicts? - Aliasgari, Majid; Kaviani, Ali; Gachkar, Latif; Hosseini-Nassab, Seyedreza (Urology Journal, 2009)
Purpose: Many environmental and occupational risk factors have been proposed for bladder cancer, among which opium consumption has been considered in few studies. We designed a study to determine the relationship between opium consumption and bladder cancer. Materials and Methods: In a retrospective, case-control study, male patients with bladder cancer, who had been referred to our hospital in a three-year period, were selected. Data regarding age, gender, smoking, and opium consumption were collected from patients’ records and compared with data of a control group, consisting of patients with benign prostatic hyperplasia (BPH). Results: Fifty-two male patients with bladder tumor (group 1) were compared with 108 patients with BPH (group2). Of the patients with bladder cancer, 36 (68%) were smokers, of whom 12 were also opium addicts. In general, 13 (25.5%) patients were opium consumers (one opium consumer was not smoker). From 108 patients with BPH, 25 (23%) were smokers, of whom, 5 were also opium addicts. Mean duration of cigarette smoking was 31 ± 13.6 and 20.2 ± 14.7 years in patients with bladder cancer and BPH, respectively. The duration of opium consumption was 11.9 ± 1.4 and 6.2 ± 1.3 years in groups 1 and 2, respectively. The duration of cigarette smoking and opium consumption in group 1 was greater than that in group 2. In addition, smoking increases the risk of bladder cancer 3.8-fold (OR = 8.3, 95% CI = 1.8 - 7.8). Simultaneous cigarette smoking and opium consumption increases the risk of bladder cancer 6.2-fold (OR = 6.2, 95% CI = 2.04 - 18.7). Conclusion: There are few studies regarding the carcinogenic effect of opium on bladder. We demonstrated that, the incidence of bladder cancer in smokers, who are simultaneously opium consumers, was higher than in patients who were only smokers. Simultaneous opium addiction and cigarette smoking may have some roles in the pathogenesis of bladder tumor. However, further studies with large sample sizes are warranted.